Video tutorial pendaftaran mobile JKN dapat meningkatkan pemahaman pasien BPJS kesehatan - Rahmayani, Kamila Zainab; Hosizah, Hosizah (Holistik Jurnal Kesehatan, 2025)
Background: The national health insurance mobile application is used for registration of social security administrator patients who want to seek treatment at health service facilities such as independent doctor's practices, but currently some patients still experience difficulties so that video tutorials can help overcome these problems. Purpose: To determine the effect of the availability of video tutorials on registering for the National Health Insurance application via mobile phones on the understanding of patients registered with the Social Security Administering Agency. Method: Quantitative research with a cross-sectional design, conducted in April 2024 at an independent doctor's practice. The sample used was 96 respondents and was collected using the accidental sampling technique. Results: Simple linear regression analysis shows that there is an influence between the availability of registration tutorial videos on the understanding of Social Security Administering Agency patients with a significant p value of 0.019 (<0.05), so that health services in this study need to provide registration tutorial videos through the National Health Insurance Mobile. Conclusion: There is a significant influence between the availability of video tutorials for registration via the National Health Insurance Mobile on the understanding of Social Security Administering Agency patients. Suggestion: Conduct routine socialization to patients who are undergoing treatment, especially Social Security Administering Agency patients who register using the National Health Insurance mobile, so that patients can understand the contents of the application.    Keywords: Health; National Health Insurance Mobile; Patients; Social Security Administering Agency; Tutorials; Video.    Pendahuluan: Aplikasi mobile Jaminan Kesehatan Nasional (JKN) digunakan untuk pendaftaran pasien badan penyelenggara jaminan sosial yang ingin berobat ke fasilitas pelayanan kesehatan, seperti praktek mandiri dokter. Namun saat ini beberapa pasien masih mengalami kesulitan, sehingga video tutorial dapat membantu mengatasi masalah tersebut. Tujuan: Untuk mengetahui pengaruh ketersediaan video tutorial tentang pendaftaran mobile JKN terhadap pemahaman pasien BPJS kesehatan. Metode: Penelitian kuantitatif menggunakan desain cross sectional, dilaksanakan pada bulan April 2024 di praktek dokter mandiri. Sampel yang digunakan sebanyak 96 responden dan dikumpulkan dengan teknik accidental sampling. Hasil: Analisis regresi linear sederhana menunjukkan bahwa ada pengaruh antara ketersediaan video tutorial tentang pendaftaran terhadap pemahaman pasien BPJS dengan nilai p signifikan 0.019 (< 0.05), sehingga layanan kesehatan pada penelitian ini perlu menyediakan video tutorial pendaftaran melalui mobile JKN. Simpulan: Ada pengaruh yang signifikan antara ketersediaan video tutorial tentang pendaftaran melalui mobile JKN terhadap pemahaman pasien BPJS. Saran: Melakukan sosialisasi rutin kepada para pasien yang berobat, terutama pasien BPJS yang mendaftar menggunakan mobile JKN, agar pasien dapat memahami isi pada aplikasi tersebut.   Kata Kunci: BPJS; Kesehatan; Mobile JKN; Pasien; Tutorial; Video.